Evaluasi Validitas dan Reliabilitas Soal Tes Uji Kemampuan Matematika Siswa Kelas IV SD Negeri Sepatan 1 - Ina Magdalena; Ika Pratiwi; Salsabila Kurniawati Putri; Siti Hilyatuddiniyah (Jurnal Halaqah, 2020)
This study aims to determine the validity and reliability of the mathematical ability test used to measure the effectiveness of mathematics learning by using modules. The tests compiled are validated by experts which include mathematics education lecturers and mathematics teachers and the results are valid and can be used without revision. Then the test was tested on the fourth-grade students of SD Negeri Sepatan 1. There were as many as 4 pieces of mathematics ability tests that were tested. Testability 1 contains ordinary fractional material consisting of 5 items. Capability test 2 contains pure fractional material 3 items. Capability test 3 contains mixed fractional material consisting of 3 items. Capability test 4 contains decimal fraction material consisting of 2 questions. Based on the test results of the ability test 1, 2, 3, and 4 analyzed with the help of SPSS version 21.00 for windows, the results obtained are based on inter-item correlation values> 0.05, which is valid. While based on the value of Cronbach's Alpha, a significance value of α> 0.05 is obtained, which is reliable. Thus the ability test items 1, 2, 3, 4 are valid and reliable.